Multidecadal variability in the North Atlantic - Sun, Jing (2021)
The North Atlantic (NA) region plays a key role in the global climate system and exhibits pronounced multidecadal climate variability. There is a controversy about the nature of the multidecadal climate variability in the NA region. This thesis provides an enhanced understanding about the multidecadal variability in the NA sector by applying and analyzing climate models and investigating observations, especially about the mechanisms for sea surface temperature (SST) and Atlantic meridional overturning circulation (AMOC) variability. Firstly, different driving factors operating on the extratropical and tropical NA SST on different timescales are investigated by using observations and model simulations. Secondly, a coupled air-sea multidecadal mode is discovered in the NA region by analyzing the fully coupled Kiel Climate Model (KCM). Thirdly, possible AMOC slowing is discussed by analyzing observational datasets and historical simulations with climate models. In the first part of this thesis, the different influences on the NA SST variability are examined based on observations and climate models. This analysis is conducted by using the basin-averaged NA SST index (NASST) and the low-pass filtered version, termed Atlantic multidecadal oscillation (AMO) index. In particular, the relationships of the two indices with some of its mechanistic drivers including Atlantic meridional overturning circulation (AMOC), North Atlantic Oscillation (NAO), subpolar gyre (SPG) and El Niño–Southern Oscillation (ENSO) are investigated. The results show that the NASST index lumps together SST variability driven by different mechanisms and operating on different timescales. Meanwhile, the AMO index emphasizes the SST variability over the extratropical NA, which is connected to the AMOC in climate models. In addition, models with a large cold bias over the NA exhibit a relatively weak linkage between the AMOC and AMO. The second part discusses the roles of ocean circulation and atmosphere-ocean coupling in the multidecadal climate ...